1983
DOI: 10.3758/bf03212306
|View full text |Cite
|
Sign up to set email alerts
|

Duration of components and response rates on multiple fixed-ratio schedules

Abstract: Pigeons were exposed to a two-component multiple fixed-ratio X fixed-ratio Y schedule of reinforcement in which X was always less than Y. Components were equal in duration and alternated at rates that varied between 2 sec and 23.6 h. Relative response rate in the FR X component: (1) increased as the duration of components increased between 2 sec and 16 min, (2) was at a maximum between 16 min and 6 h, and (3) decreased as the duration of components increased from 6 h to 23.6 h. The changes in relative response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Relative rate of responding decreased as components were lengthened; however, there was no systematic effect of component duration on absolute rate of responding in the richer or leaner components, and repeatability at the replications of the 10-s conditions was poor. This suggests that, despite the significant trend for relative rate to change as components were those of others (McSweeney et al, 1986;White, Pipe, McLean, & Redman, 1985) (Norborg et al, 1983 The finding that relative response rate increased as a function of increasing component duration may also provide an explanation for results from the only published study that has examined mult VI VI performance in a closed economy (Elliffe & Davison, 1985). In that study only one component duration was used (150 s), and it was suggested that closed economy multiple-schedule performance could be characterized by generalized matching exponents of 1.5 (overmatching).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative rate of responding decreased as components were lengthened; however, there was no systematic effect of component duration on absolute rate of responding in the richer or leaner components, and repeatability at the replications of the 10-s conditions was poor. This suggests that, despite the significant trend for relative rate to change as components were those of others (McSweeney et al, 1986;White, Pipe, McLean, & Redman, 1985) (Norborg et al, 1983 The finding that relative response rate increased as a function of increasing component duration may also provide an explanation for results from the only published study that has examined mult VI VI performance in a closed economy (Elliffe & Davison, 1985). In that study only one component duration was used (150 s), and it was suggested that closed economy multiple-schedule performance could be characterized by generalized matching exponents of 1.5 (overmatching).…”
Section: Discussionmentioning
confidence: 99%
“…The main question addressed by the present experiment is whether the differences in results between Norborg et al (1983) In the present experiment, the same subjects were exposed to both types of economies. To facilitate comparison with previous studies that have examined the effects of component duration on responding, body weights for subjects in the open economy were maintained at 80% of freefeeding weights; for subjects in the closed economy, no deprivation regimen was used.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Other examples exist in the literature (e.g., Collier, Hirsch, & Hamlin, 1972;Findley, 1959) and other experiments with rats have extended it (see Hursh & Natelson, 1981). The distinction between open and closed economies has become common (see Brady, 1982;Collier, 1983;Delius, 1983;Lucas, 1981;Mellitz, Hineline, Whitehouse, & Laurence, 1983;Norborg, Osborne, & Fantino, 1983;Rachlin, 1982).…”
Section: Analogy Kurtmentioning
confidence: 97%
“…Time series line graphs must have a unit of time on the horizontal axis (Robbins 2005). Examples of units of time range from seconds (e.g., Preston 1994) and minutes (e.g., Norborg et al 1983) to hours (e.g., Ramirez 1997) and days (e.g., Gutentag and Hammer 2000). Twenty-eight percent of line graphs in behavioral journals maintained a time unit label.…”
Section: Essential Structurementioning
confidence: 99%